Γδ T cells support gut Ag‐reactive colitogenic effector T‐cell generation by enhancing Ag presentation by CD11b+ DCs in the mesenteric LN. Issue 2 (7th December 2015) - Do, Jeongsu; Visperas, Anabelle; Freeman, Michael L.; Jang, Eunjung; Kim, Sohee; Malissen, Bernard; Min, Booki
Abstract : T cells expressing the γδ TCR are dominant T‐cell subsets in the intestinal immune system. We previously demonstrated that γδ T cells play important roles in augmenting Th17‐type colitogenic immune responses in a T‐cell‐induced colitic inflammation model. However, its underlying mechanism remains poorly understood. In this study, an in vitro coculture system using effector T cells enriched in gut Ag‐reactive cells was employed as a readout tool to search for gut Ag presenting APCs. We found that the presence of γδ T cells dramatically enhances gut Ag presentation within the mLN in mice. Gut Ag presentation by CD11b + DC subsets was particularly controlled by γδ T cells. Interestingly, γδ T‐cell entry to the lymph nodes was essential to improve the Ag presentation. Therefore, our results highlight that γδ T cells play a previously unrecognized role to support colitogenic immunity by regulating gut Ag presentation in the draining LN.